AN IMPLEMENTATION OF PARTICIPATIVE IQRO METHOD IN THE ORIENTED OF AL-QURAN EDUCATION CENTER ON THE PURPOSE OF LEARNING GOAL AND OBJECTIVES FOR EARLY CHILDREN - Chandra Asri Windarsih (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2019)
Learning to read and write the Quran using the IQRO method has been used for a long time and applied to children. The basic reason is that with IQRO it is very easy for children to follow, the book is cheap consisting of six books that have a certain level. This research wants to collaborate with the learning goal method and objectives oriented. Hopefully, that early childhood is easy to understand and easy to remember letters, to be able to read the Quran correctly. Formulation of the problem "How is the application of participatory learning IQRO method in TPQ oriented to the purpose of learning activities for early childhood". The objective of the research is to find the general description, planning, implementation, and evaluation, participatory learning of the IQRO method in TPQ through the Learning Goal Method and Objectives Oriented on children. This research used a qualitative method with analytical descriptive. The researcher analyzes data, find information, relationships, basic frameworks, carefully compare, and report in narrative form. The result is that children who are included in participating and have goals in IQRO learning will be able to more quickly and master learning. Location of research in TPQ (Alquran Education Center) Assalam Pakusarakan Earth Complex II Rt 03/25 Tanimulya Ngamprah Kab. West Bandung.